2023
DOI: 10.1042/bsr20221519
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of novel automatable assay for cholesterol efflux capacity

Abstract: During the past decade, evaluation of high-density lipoprotein (HDL) functionality has been well studied for predicting cardiovascular disease risk. Cholesterol efflux capacity (CEC) is the strongest candidate as the biomarker out of various HDL anti-atherosclerotic functions. However, CEC has not yet been introduced clinically because of several technical issues, including the use of radioactive materials and differentiated cells in the assay. Previously, our laboratory developed a radioisotope- and cell-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors of the research we are referencing, note that the traditional CEC measurement technique necessitates cultured cells and radioisotope-labeled cholesterol, both of which are impractical in clinical settings given large number of clinical samples to be analyzed. In their prior study, they created a CEC assay to circumvent this issue by using gel beads and apolipoprotein B-100-depleted serum (BDS) in place of cells and radioisotopes [ 22 ]. Unfortunately, their earlier procedure required the centrifugation step to spin down the gel beads and to separate cholesterol from supernatant that was fluorescently labeled [ 23 ].…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of the research we are referencing, note that the traditional CEC measurement technique necessitates cultured cells and radioisotope-labeled cholesterol, both of which are impractical in clinical settings given large number of clinical samples to be analyzed. In their prior study, they created a CEC assay to circumvent this issue by using gel beads and apolipoprotein B-100-depleted serum (BDS) in place of cells and radioisotopes [ 22 ]. Unfortunately, their earlier procedure required the centrifugation step to spin down the gel beads and to separate cholesterol from supernatant that was fluorescently labeled [ 23 ].…”
Section: Commentarymentioning
confidence: 99%
“…Before ILM is used in the laboratory diagnostic settings, its stability should also be examined. The authors, therefore, assessed the ILM’s stability and their findings showed that the ILM solution was stable for 45 days at 4 degrees [ 22 ].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation